TRANSLATION PROBLEMS OF PROVERBS WITH HYDRONYM COMPONENTS IN ENGLISH AND UZBEK LANGUAGES - Kayumova Shakhnoza Kobiljonovna (Journals Park Publishing, 2024)
This article explores the translation challenges of proverbs containing hydronyms – place names or water body names (such as rivers, seas, and lakes) –between English and Uzbek. Proverbs are deeply embedded in cultural contexts, and hydronyms in these sayings often carry symbolic and metaphorical meanings that are specific to the historical settings of a language. The article also examines the linguistic, cultural, and conceptual difficulties that arise when translating proverbs with hydronym components from English to Uzbek and vice versa. It also discusses translation strategies such as substitution, literal translation with explanation, and adaptation, which can help preserve the essence of the original proverb while making it meaningful to the target audience.
Keywords: Proverbs, hydronyms, translation problems, linguistic differences, cultural significance, cross-cultural translation, translation strategies, substitution, literal translation, adaptation.